Delayed buccal fat pad herniation: An unusual complication of buccal flap in cleft surgery - Puneet Tuli (Indian Journal of Plastic Surgery, 2009)
Buccal musculomucosal flap is commonly used in cleft palate surgery for providing additional lining when nasal mucosa is inadequate. We report an unusual complication of progressively increasing fat herniation from the sutured donor site which started appearing on the third postoperative day. This necessitated excision of the protruding fat pad on the seventh postoperative day. The possible mechanism and precautions for prevention of this complication are discussed.